ON THE FOOD FUNCTION OF THE MODERN RUSSIAN STATE - A. Mokhov (Гуманитарные и юридические исследования)
The article outlines the main theoretical aspects of the designation of food functions (functions to ensure food security), as one of the modern functions inherent in the Russian state. The variety of directions of modern government, modern challenges and global problems necessitate the allocation of new separate functions necessary for the state to fulfill its social obligations. The independence of the food function is justified by the author with regard to its compliance with the main features of the state function outlined in science: the presence of special organizational and legal means and methods of implementation, relevance to any stage of the state's historical development, awareness of food security as an independent public administration sphere, and food security to determine and comply with the social purpose of the state. In accordance with international legal acts on food security issues, the implementation of the food function should occur not only in the context of social security, but also by regulating the agro-industrial complex, the land market, and other factors. The objectives of the implementation of the food function of the Russian Federation include the guarantee of the right to food, which is part of the constitutional right of everyone to decent living conditions, the realization of public interest (ensuring food security as an integral part of national security). The opinion is expressed on the need to adopt a unified Federal Law "On Food Security of the Russian Federation", which will reflect the basic principles and directions for the implementation of the food function of the state.